The Influence of Website Quality on Online Purchase Intentions on Agoda.Com with E-Trust as a Mediator - Damayanti Octavia; Andes Tamerlane (Binus Business Review, 2017)
In e-commerce market, there is no physical interaction between buyers, sellers, and payments. The confidence to buy online e-trust can raise or lower the perceived risk and security issues, so e-trust is crucial for the success of e-commerce companies, such as Agoda.com. The sorting of online businesses is vital to avoid losses when doing the online business transaction, such as by looking at the quality of the website and the company’s ability to provide e-trust. The methods used in this research were quantitative and causal. The research sample was collected using non-probability sampling method which was purposive sampling by taking 200 respondents. Data analysis techniques used SEM (Structural Equation Modeling).The conclusion shows the existence of a significant influence on the website’s quality towards e-trust, and e-trust on the online purchase intentions. Moreover, there is an insignificant impact on the quality of the site towards online purchase intentions.